2011
DOI: 10.1038/hr.2011.35
|View full text |Cite
|
Sign up to set email alerts
|

Eplerenone potentiates protective effects of amlodipine against cardiovascular injury in salt-sensitive hypertensive rats

Abstract: The clinical value of the combination of amlodipine and eplerenone is unclear. This study was undertaken to test whether eplerenone potentiates the protective effects of amlodipine against hypertensive cardiovascular injury. Salt-loaded Dahl salt-sensitive hypertensive rats (DS rats) were given (1) vehicle, (2) an antihypertensive dose of amlodipine, (3) a non-antihypertensive dose of eplerenone or (4) combined amlodipine and eplerenone for 6 weeks, and the effects on cardiovascular injuries were compared. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…A recent study in a rat model of salt-sensitive hypertension found that eplerenone treatment potentiated the protective effects of the L-type calcium channel blocker amlodipine against cardiovascular injury. This finding supports that MRA/L-type calcium channel blocker combination therapy could potentially reduce the cardiovascular morbidity and mortality in hypertensive patients more effectively than either drug alone and at lower doses that might limit side effects [90]. In addition, hypertension is predominantly a disease of the elderly, affecting more than 60% of people over 60 years of age and up to 80% of the growing population over 80.…”
Section: Mr and Hypertension: The Vasculature As Culprit In Elevated supporting
confidence: 66%
“…A recent study in a rat model of salt-sensitive hypertension found that eplerenone treatment potentiated the protective effects of the L-type calcium channel blocker amlodipine against cardiovascular injury. This finding supports that MRA/L-type calcium channel blocker combination therapy could potentially reduce the cardiovascular morbidity and mortality in hypertensive patients more effectively than either drug alone and at lower doses that might limit side effects [90]. In addition, hypertension is predominantly a disease of the elderly, affecting more than 60% of people over 60 years of age and up to 80% of the growing population over 80.…”
Section: Mr and Hypertension: The Vasculature As Culprit In Elevated supporting
confidence: 66%
“…Calcium channel blockers decrease aldosterone synthesis in human adrenocortical cells [24] and in hypertensive patients [25]. Nakamura et al reported that eplerenone potentiates the protective effects of amlodipine against cardiovascular injury in salt-sensitive hypertensive rats independently of blood pressure [26]. In this study, 30-40% of patients needed to use amlodipine to achieve BP <140/90 mmHg.…”
Section: Discussionmentioning
confidence: 64%
“…However, Cav1 interacts with MR and form a MR/Cav1 complex, which mediates a rapid signaling cascade of oxidation initiated by aldosterone [10]. Aldosterone induced more abundant of MR/Cav1 complexes to interacted with NOX4, leading to oxidation [34]. These indicate that the effects of Cav1 on redox modification may be different with a variety of cell types.…”
Section: Discussionmentioning
confidence: 99%